Interval optimal control for uncertain problems - Leal, Ulcilea; Lodwick, Weldon; Silva, Geraldo [UNESP]; Maqui-Huamán, Gino G. (Elsevier, 2019)
This paper addresses optimal control problems with an interval-valued objective function. We consider the lower and upper order relation on the interval space and with this order relation we obtain optimality conditions. Using two different derivative concepts we propose necessary and sufficient conditions for the interval optimal control problems. Some numerical examples are presented.
Keywords: Interval optimal control; Interval-valued functions